2019
DOI: 10.1088/2058-6272/ab079b
|View full text |Cite
|
Sign up to set email alerts
|

E-beam generation in discharges initiated by voltage pulses with a rise time of 200 ns at an air pressure of 12.5–100 kPa

Abstract: The effect of air pressure (12.5, 25, 50, and 100 kPa) on the generation of runaway electron beams in a non-uniform electric field when applying voltage pulses (≈35 kV) with a rise time of ≈200 ns has been studied. The results show that the discharge has various stages: streamer, diffuse, and spark. Initially, a wide streamer develops in the gap and a diffuse discharge is formed. A spark is formed ≈100 ns after the breakdown. The current pulse of a supershort avalanche electron beam (SAEB) was measured with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
1
6
0
1
Order By: Relevance
“…The generators were connected to discharge chambers with centimeter gaps. Figure 1 shows two experimental setups with generators (GIN-55-01, GIN-100-1, GIN-50-1, NPG-15/2000N, NPG-18/2000N and GIN-35NP) rated at an amplitude of tens of kilovolts [68].…”
Section: Experimental Setups and Measuring Techniquesmentioning
confidence: 99%
“…The generators were connected to discharge chambers with centimeter gaps. Figure 1 shows two experimental setups with generators (GIN-55-01, GIN-100-1, GIN-50-1, NPG-15/2000N, NPG-18/2000N and GIN-35NP) rated at an amplitude of tens of kilovolts [68].…”
Section: Experimental Setups and Measuring Techniquesmentioning
confidence: 99%
“…However, it was found that REs can be generated not only in the prebreakdown stage [36]. The generation of REs can occur after bridging the gap with plasma.…”
Section: Resmentioning
confidence: 99%
“…In recent experimental studies, it was found that REs can be generated not only in the prebreakdown stage of the discharge, but also after breakdown [36] when microsecond voltage pulses with an amplitude of several tens of kilovolts are applied. This indicates that even after filling the discharge gap with plasma, the reduced electric field strength can locally exceed the critical value required for electron runaway.…”
Section: Introductionmentioning
confidence: 99%
“…where ε is the kinetic energy of electrons, x is the location of electrons, E is the local electric field and = F friction + F F ionization radiation is the friction force caused by inelastic the friction force of electrons moving in gases will be less than the electric field force. Electrons gain energy from electric field continuously and enter the 'fast' or 'runaway' state [24].…”
Section: Discussionmentioning
confidence: 99%